2022
DOI: 10.1002/art.42345
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences in Cancer‐Associated Myositis

Abstract: Idiopathic inflammatory myopathies (IIMs) comprise a heterogeneous group of rare immune‐mediated disorders that primarily affect muscles but also lead to dysfunction in other organs. Five different clinical subphenotypes of IIM have been distinguished: dermatomyositis, polymyositis, inclusion body myositis, antisynthetase syndrome, and immune‐mediated necrotizing myopathy. Excess mortality and morbidity associated with IIM are largely attributed to comorbidities, particularly cancer. The risk of malignancy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…Classically, those with juvenile dermatomyositis tend to have more vasculopathy, calcinosis, and ulceration but overall better prognosis. In adults, there is a high risk of malignancies, interstitial lung disease, and amyopathic disease (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Classically, those with juvenile dermatomyositis tend to have more vasculopathy, calcinosis, and ulceration but overall better prognosis. In adults, there is a high risk of malignancies, interstitial lung disease, and amyopathic disease (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…HLA-B*08:01 confers risk of DM and also for lung cancer (15,39). A recent review on genetic influences in cancer-associated myositis addressed similar oncogene expression profiles between DM and several hematologic and solid malignancies (40). Smoking has been suggested as a risk factor of IIM, acute myeloid leukemia, lung cancer, and liver cancer (5,7).…”
Section: Discussionmentioning
confidence: 99%
“…Dermatomyositis (DM), an uncommon chronic autoimmune disease, is a kind of idiopathic inflammatory myopathy (IIM) characterized by muscle pain and weakness, unique skin findings, such as heliotrope rash, or gottron's papules, or gottron's sign, or V‐sign or shawl sign, etc 1 . In recent years, a relationship between DM and malignancy has been well established 2,3 . Immune dysfunction, chronic inflammation, older age and immunosuppressive therapy for DM have been linked to an increased incidence of malignancy 4 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 In recent years, a relationship between DM and malignancy has been well established. 2 , 3 Immune dysfunction, chronic inflammation, older age and immunosuppressive therapy for DM have been linked to an increased incidence of malignancy. 4 It has been reported that malignancies are detected in approximately 10%–47% of DM patients and associated with high mortality.…”
Section: Introductionmentioning
confidence: 99%